2018
DOI: 10.1002/ijc.32024
|View full text |Cite|
|
Sign up to set email alerts
|

Regulatory T cells expressing abundant CTLA‐4 on the cell surface with a proliferative gene profile are key features of human head and neck cancer

Abstract: FOXP3+ regulatory T (Treg) cells suppress anti‐tumor immunity. The suppression of Treg cells is regulated by cytotoxic T‐lymphocyte‐associated antigen‐4 (CTLA‐4), whose expression on the cell surface is tightly regulated. Here we found that Treg cells expressing abundant CTLA‐4 on the cell surface (surface‐CTLA‐4+ Treg) were expanded in human head and neck cancer tissues. RNA sequencing of surface‐CTLA‐4+ and surface‐CTLA‐4− Treg cells infiltrating human head and neck cancer tissues revealed that surface‐CTLA‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 53 publications
(131 reference statements)
3
59
0
Order By: Relevance
“…This was done on few samples because of sample limitation and technical difficulty to generate libraries from very few cell numbers. Similarly, CTLA-4 + and CTLA-4 − Tregs from head and neck cancer patients were compared in very small number of samples [21]. We found that the hierarchical clustering of differentially expressed genes showed distinct cluster of TIM-3 + and TIM-3 − T cells ( Figure 3A).…”
Section: Transcriptomic Profile Of Cd4 + Tim-3 + Tils Reveals Their Pmentioning
confidence: 88%
“…This was done on few samples because of sample limitation and technical difficulty to generate libraries from very few cell numbers. Similarly, CTLA-4 + and CTLA-4 − Tregs from head and neck cancer patients were compared in very small number of samples [21]. We found that the hierarchical clustering of differentially expressed genes showed distinct cluster of TIM-3 + and TIM-3 − T cells ( Figure 3A).…”
Section: Transcriptomic Profile Of Cd4 + Tim-3 + Tils Reveals Their Pmentioning
confidence: 88%
“…In HNSCC the amount of certain immune cell populations and expression levels of various activation and suppressive markers on their cell surface might be altered. Most studies agree that increased Treg infiltration (specifically defined Treg subpopulations expressing various activation markers such as CTLA4, PD-1 or Helios) or increased infiltration of CD4 or CD8 T cells expressing PD-1 is a negative prognostic marker [40,41] in HNSCC, while the presence of memory CD103+ T cells or Tbet+ Tregs correlate with a better prognosis [42,43]. Circulating Treg cells were correlated with negative clinicopathological findings and worse prognosis [44,45,46], on the other hand increased levels of circulating Th17 cells were considered a good prognostic indicator [47].…”
Section: Discussionmentioning
confidence: 99%
“…This could be due to the lower percentage and lower expression level of MDSC subsets in some TT and NT samples. Similarly, CTLA-4 + and CTLA-4 − Tregs from head and neck cancer patients were compared in very small number of samples [56]. The cDNA libraries were generated using QIAseq FX Single Cell RNA Library Kit (Qiagen, Hilden, Germany) following the manufacturer's instructions.…”
Section: Library Preparationmentioning
confidence: 99%